2017
DOI: 10.1186/s12894-017-0255-x
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters and related factors in bladder cancer patients three months after radical cystectomy

Abstract: BackgroundTo identify symptom distress and clusters in patients 3 months after radical cystectomy and to explore their potential predictors.MethodsA cross-sectional design was used to investigate 99 bladder cancer patients 3 months after radical cystectomy. Data were collected by demographic and disease characteristic questionnaires, the symptom experience scale of the M.D. Anderson symptom inventory, two additional symptoms specific to radical cystectomy, and the functional assessment of cancer therapy questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
3
25
0
1
Order By: Relevance
“…Three factors—gender, stage of disease and resilience—were correlated with the severity of the four symptom clusters. As found by Akin, Can, Aydiner, Ozdilli, and Durna () and Ren, Tang, Zhao, and Ren (), female patients report more severe symptoms than male patients. This may be related to women's weaker physical function and to the fact that they have a higher willingness to report more severe symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Three factors—gender, stage of disease and resilience—were correlated with the severity of the four symptom clusters. As found by Akin, Can, Aydiner, Ozdilli, and Durna () and Ren, Tang, Zhao, and Ren (), female patients report more severe symptoms than male patients. This may be related to women's weaker physical function and to the fact that they have a higher willingness to report more severe symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Of the 23 studies included in this review, 13 used a cross-sectional design to identify symptom clusters in oncology patients receiving chemotherapy (online supplemental table 1). Seven studies were conducted in the USA,29 32–37 two in China,38 39 two in Thailand,40 41 one in Austria,42 and one in Turkey 43. Sample sizes ranged from 9641 to 1328 29.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated for symptom clusters in patients with heterogeneous types of cancer 29 32 33 35 42. Of the eight studies that evaluated for clusters in patients with homogeneous types of cancer, four evaluated patients with breast cancer,34 36 40 41 one with bladder cancer,39 one with leukaemia,38 one with lymphoma,43 and one with lung cancer 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Li et al's research on head and neck cancer patients with endotracheal tubes revealed that there was no significant difference in the scores of QoL between the high and low severity groups of the digestive symptom cluster (47). These contradictory results may be related to disease characteristics, treatment modalities, and the different study periods investigated (49,50). As there have been few studies of symptom clusters focused on cervical cancer, our study provides new evidence to support that symptom clusters might be reliable predictors of QoL in this population.…”
Section: Discussionmentioning
confidence: 98%